Extracellular Vesicles: A New Nano Tool for the Treatment of Inflammatory Bowel Diseases - Tandra, Nitin; Wu, Peipei; Hu, Xinyuan; Mao, Fei; Xu, Wenrong; Qian, Hui (Current Nanoscience, 2019)
The intestinal tract is a complex and important physiological and immunological organ. Intestinal tract homeostasis requires a series of coordinated interactions involving gut microbiota, the crypt intestinal stem cells (ISC) and the surrounding niche, including the intestinal epithelial cells, endothelial cells, dendritic cells, and macrophages. The destruction of intestinal homeostasis leads to autoimmune diseases, such as inflammatory bowel disease (IBD). IBD is a non-specific, and remittent- relapsing inflammatory disorder of the gastrointestinal tract. There is no effective method to keep patients in remission for a long term. It has been reported that extracellular vesicles (EVs) exert immune activation and immunosuppressive effects in the pathogenesis of IBD. In order to explore new therapeutic strategies for IBD, in this review, we summarize the observations on the immune properties and functions of EVs in intestinal mucosal immunity.
Keywords: extracellular vesicles